2016
DOI: 10.1007/s10549-016-3792-1
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency of germline DNA genetic findings in an unselected prospective cohort of triple-negative breast cancer patients participating in a platinum-based neoadjuvant chemotherapy trial

Abstract: We describe the status and frequency of germline DNA genetic findings in an unselected prospective cohort of triple negative breast cancer patients participating in a platinum-based neoadjuvant chemotherapy trial. Study population includes 124 consecutive patients with stage II-III TNBC from a trial exploring the antitumor activity of neoadjuvant carboplatin/docetaxel chemotherapy enrolled between 2012 and March 2015, to determine the frequency of germline DNA genetic mutations. 17.1 % of the patients with ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
3
27
0
1
Order By: Relevance
“…In summary, even TNBC cases unselected for a positive family history of cancer and/or early disease onset appear to be enriched for deleterious germline mutations in BRCA1/2 . In other studies, the BRCA1/2 mutation frequencies of unselected TNBC patients vary between 9.4 and 18.2% (table 1) [26,27,29,30,31,35,36,37]. …”
Section: Elevated Prevalence Of Brca1/2 Mutations In Tnbcmentioning
confidence: 96%
“…In summary, even TNBC cases unselected for a positive family history of cancer and/or early disease onset appear to be enriched for deleterious germline mutations in BRCA1/2 . In other studies, the BRCA1/2 mutation frequencies of unselected TNBC patients vary between 9.4 and 18.2% (table 1) [26,27,29,30,31,35,36,37]. …”
Section: Elevated Prevalence Of Brca1/2 Mutations In Tnbcmentioning
confidence: 96%
“…LGRs were also detected (Table 2) [52,53]. The third publication tested for LGRs in 16 hereditary BC patients but did not test for pathogenic point mutations.…”
Section: The Scope Of Brca1 and Brca2 Mutations In Central And South mentioning
confidence: 99%
“…BARD1 participates in important cellular processes such as DNA repair, RNA processing, transcription, cell cycle regulation and apoptosis [65]. Studies on BARD1 were performed in Chile and Peru (Table 5) [53,66]. Gonzalez-Hormazabal et al [66] reported that in Chilean women negative for BRCA1/2 mutations, BARD1 Cys557Ser was associated with increased risk of BC.…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
See 2 more Smart Citations